The dimerization motif of the glycophorin A transmembrane segment in membranes: importance of glycine residues. - Brosig, B. (Cold Spring Harbor Laboratory Press, 1998)
The glycophorin A transmembrane segment homo-dimerizes to a right-handed pair of alpha-helices. Here, we identified the amino acid motif mediating this interaction within a natural membrane environment. Critical residues were grafted onto two different hydrophobic host sequences in a stepwise manner and self-assembly of the hybrid sequences was determined with the ToxR transcription activator system. Our results show that the motif LIxxGxxxGxxxT elicits a level of self-association equivalent to that of the original glycophorin A transmembrane segment. This motif is very similar to the one previously established in detergent solution. Interestingly, the central GxxxG motif by itself already induced strong self-assembly of host sequences and the three-residue spacing between both glycines proved to be optimal for the interaction. The GxxxG element thus appears to be the most crucial part of the interaction motif.